Pengaruh Variabel Fundamental Terhadap Struktur Modal Dan Dampaknya Terhadap Nilai Perusahaan - Utomo, Prastyo; Djumahir (Jurnal Aplikasi Manajemen, 2013)
This study aims to examine the influence of fundamental variables that measured by profitability, firm size, growth opportunities, assets structure, non-debt tax shield and earnings volatility on the capital structure and analyze the effect of capital structure on firm value. Data analysis was performed on textile and garment companies listed in Indonesia Stock Exchange during the period 2005-2012. Results of data analysis using a two-stage regression analysis showed that profitability, asset structure and earnings volatility has significant effect to capital structure, while no significant effect was found between firm size, growth opportunities and non-debt tax shield against the company's capital structure. Results of this study also found that capital structure didn’t have significant effect to firm value.